Peanuts, Corn, And Other Cereal Grains Can Be Toxic To Wild Birds - Kristen L. Candelora; William M. Giuliano (EDIS, 2005)
It is nearly impossible to harvest 100% of any crop. Often what is left over remains on the ground, available to wild birds as a potential source of food. However under certain circumstances, eating these “leftovers” can pose a serious health risk to wild birds. The reason for this is that peanuts, corn, and other cereal grains may grow a fungus/mold that produces poisons called mycotoxins. These mycotoxins can be deadly to the wild birds that feed on them (Figure 1). The fungi can grow on the unharvested crops left behind, or on harvested crops during storage and transportation. There are many different types of mycotoxins and susceptibility to each seems to vary from species to species. Although domestic and wild animals may be affected, this document will focus on the effects of mycotoxins on wild birds. This document is WEC 190 and is one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: May 2005.